Gender Ratio Analysis in Rawalpindi and Islamabad: Causes and Consequences - Razzaq, Anjum; Afzal, Muhammad; Rauf, Abdur; Ahmad, Sahibzada Yaseen (Asian Development Policy Review, 2018)
Population growth and its relevant dynamics have always remained an important subject for policy makers. It is a common observation that the within this population the gender gap is wider in developing countries than developed world. The case of gender ratio in Pakistan is severe and distressing. Current study attempted to analyze the causes and consequences of gender ratio in Pakistan. The analysis suggest that the phenomenon of gender ratio is wide and can be observed in every walk of life. This study suggested that gender gap can be reduced by taking concrete steps at micro and macro level.